Association Between the Morphology of Proximal Tibiofibular Joint and the Presence of Knee OA - Qi, Xin-Zheng; Wang, Min; Zhang, Bo; Nie, Mao-Dan; Ma, Xiao-Ying; Wang, Hui-Zhi; Wang, Xiao-Hong; Cheng, Cheng-Kung; Zhang, Min (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: The aim of this study was to evaluate the association between the morphology of the proximal tibiofibular joint (PTFJ) and the presence of knee osteoarthritis (OA). Methods: 28 OA subjects and 30 healthy subjects were enrolled in this study. A 3D model of the lower limb of each subject was constructed from CT scans and used to measure the characteristics of the PTFJ, including the shape of the articular facets, articular surface area, joint inclination, relative articular height and joint declination. The association between the characteristics of the PTFJ and presence of knee OA was assessed using binomial logistic regression analysis. Results: There was a significant difference between the OA and healthy groups in terms of the inclination (p=0.028) and declination (p=0.020) of the PTFJ and relative articular height (p=0.011). A greater inclination angle (OR: 1.463, 95% CI: 1.124-1.582, p = 0.021), greater declination angle (OR: 1.832, 95% CI: 1.691-2.187, p = 0.009) and lower relative articular height (OR: 0.951, 95% CI: 0.826 - 0.992, p = 0.008) were found to be associated with an increased likelihood of knee OA being present. Conclusion: The results of this study suggest that abnormal PTFJ morphology is associated with the presence of knee OA.